(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2021)
A series of novel 1,2,4- Triazole was synthesized and investigated for antimicrobial activity. The structures of all synthesized compounds were confirmed by means of elemental analysis, IR, 1H NMR, and LCMS. All compounds were evaluated for antimicrobial activity cup plate method against S. aureus, B. anthracis, P. aeruginosa, E. coli, C. albicans and A. niger. Compounds 3a, 3b and 3e showed mild to moderate activity, whereas compound 3c and 3d showed significant activity against gram positive bacteria. In case of antifungal activity, compounds 3b and 3c showed mild to moderate activity against the fungal strains as compared with fluconazole. The predicted results showed that all of the compounds (3a-3f) may not have overall toxicity and any other kind of toxicity and showed great % absorbance ranging from 93.25 to 94.22 %.